2023
DOI: 10.47363/jnrrr/2023(5)178
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen and Outcomes Following the Brain Injury: A Systematic Review

Javed Iqbal,
Abdullah Naeem

Abstract: Multiple sclerosis (MS) is an inflammatory disease of the central nervous system, characterized by neurological deficits. While the etiology of MS remains unclear, both genetic and environmental factors are known to play a role. Elevated levels of IL-12p40 have been observed in the cerebrospinal fluid and serum of MS patients, and it has been suggested that genetic variants in the IL-12B gene may contribute to MS susceptibility and/or pathogenesis. In this study, we investigated the association between MS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…There is a growing body of evidence showing benefits with HBO2 in post-stroke patients, including post-stroke memory impairment ( 23 ), cognitive impairment ( 24 ), traumatic brain injury ( 25 , 26 ), and chronic neuropathic pain ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of evidence showing benefits with HBO2 in post-stroke patients, including post-stroke memory impairment ( 23 ), cognitive impairment ( 24 ), traumatic brain injury ( 25 , 26 ), and chronic neuropathic pain ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a review of four studies, the authors concluded that HBO2 is effective for ischemic strokes ( 26 ).…”
Section: Discussionmentioning
confidence: 99%